The influence of means ends analysis (MEA) model on grammar achievement - Tri Rositasari; Finza Larasati; Dwi Rara Saraswaty (English Review: Journal of English Education, 2020)
The objective of this study was to find out the influence of MEA learning model on students’ grammar learning achievements. The participants were the third semester students of English study program, UM Palembang in academic year 2019/2020 which amounted to 40 students. This study was a quantitative research. This study used pre-experimental method. The research design used two groups pretest post-test design. The researcher conducted several steps to analyze the data; first, data from pre- and post-test results were analyzed to find averages obtained from the control and experimental group. Second, the data obtained by the control and experimental group were compared statistically to determine differences in grammar test scores between the two groups using paired sample tests. Third, the data obtained from the second step were compared statistically to find the significant differences in the grammar values between the two groups by using paired sample t-tests. Based on the results of the study, it can be concluded that the experimental group before the treatment was carried out in the learning process based on the pretest value was still not good, but when the treatment has been carried out, the student post-test results showed a very good improvement. For the control group, there were no favorable changes (significant) between the pre- and post-test result scores, because both of them showed the same results, which were not good.